Effects of unilateral and bilateral eccentric training on lower limb maximal strength, jump, and sprint performance in trained adolescent male basketball players: a randomized controlled trial - Wu, B.; Hu, J.; Hu, S.; Liu, Z.; Yin, M.; Xu, K.; Tao, M.; Yue, L.; Liu, H.; Chen, A.; Song, Z. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Basketball requires a solid foundation of lower limb strength and explosive power. Unilateral and bilateral resistance training modes may differ in improving sport-specific performance, but their relative effects and potential advantages in trained adolescent athletes remain unclear. This pilot study aims to explore the application effects of these two methods on specific performance indicators.